The Impact of Sunrise Land Lombok Beach Development on the Social Economy of the Community in Labuhan Haji Village, East Lombok Regency: Dampak Pembangunan Pantai Sunrise Land Lombok Terhadap Sosial Ekonomi Masyarakat Desa Labuhan Haji Kabupaten Lombok Timur - Denda Laila Prihandini; Akung Daeng; Satarudin, Satarudin; Bjorn Schelander (Tinta Emas Publisher, 2023)
Indonesia is a country that has a variety of cultures and abundant natural beauty. Natural resources as an important asset for the country by being utilized as a tourism location. The purpose of this study was to analyze the economic (income) and social (education) differences of the community before and after the construction of the Sunrise Land Lombok beach in the village of Labuhan Haji, Labuhan Haji sub-district, East Lombok district. This type of research uses descriptive quantitative research with a population of 25 with a survey method because all populations are used as respondents. Data analysis method with multiple linear regression analysis model with the help of SPSS software. The results of the study show that the construction of the Sunrise Land Lombok beach in Labuhan Haji village, Labuhan Haji sub-district, East Lombok district is proven to have th = -7.9 less than t0.025, 4 = -2.0639, so H0 is rejected, meaning that the average net income the community after the construction of the sunrise land beach is greater than the average net income of the community before the construction of the sunrise land beach lombok.